Predictors of competitive achievement among pubescent synchronized swimmers: an analysis of the solo-figure competition - Peric, M.; Cavar, M.; Zenic, N.; Sekulic, D.; Sajber, D. (The Journal of Sports Medicine and Physical Fitness, 2014)
Aim: This study examined the applicability of sport-specific fitness tests (SSTs), anthropometrics, and respiratory parameters in predicting competitive results among pubescent synchronized swimmers. Methods: A total of 25 synchronized swimmers (16-17 years; 166.2±5.4 cm; and 58.4±4.3 kg) volunteered for this study. The independent variables were body mass, body height, Body Mass Index (BMI), body fat percentage (BF%), lean body mass percentage, respiratory variables, and four SSTs (two specific power tests plus one aerobic- and one anaerobic-endurance test). The dependent variable was competitive achievement in the solo figure competition. The reliability analyses, Pearson`s correlation coefficient and forward stepwise regression were calculated. Results: The SSTs were reliable for testing fitness status among pubescent synchronized swimmers. The forward stepwise regression retained two SSTs, BF% and forced vital capacity (FVC, relative for age and stature) in a set of predictors of competitive achievement. Significant Beta coefficients are found for aerobic-endurance, SST and FVC. Conclusion: The sport-specific measure of aerobic endurance and FVC appropriately predicted competitive achievement with regard to the figures used in the competition when competitive results (the dependent variable) were obtained. Athletes and coaches should be aware of the probable negative influence of very low body fat levels on competitive achievement.